(untitled) (Географический вестник=Geographical bulletin, 2017)
Рассмотрены варианты оценки обмена вод в искусственных водоемах. Внутренний водообмен в морфоучастках Камского и Воткинского водохранилищ представлен в многолетнем аспекте с использованием модели В.А. Знаменского. INTERNAL WATER EXCHANGE OFKAMAWATER BASINS CASCADE (ON V.A.ZNAMENSKY MODEL) On the basis of the analysis of long-term data on internal water exchange within the limits of morfometric sites of Kama and Votkinsk water basins it is established, that change of an exchange of waters depends from magnitude of year runoff; internal-year a course of water exchange on Votkinsk water basin depends on operating mode of Kama and Votkinsk hydroelectric power station; amplitude of fluctuations of an exchange of waters on Votkinsk the water basin is essential less, than on Kama water basins, that is connected with cascade position.